Calibration of the Advanced Spectral Leakage scheme for neutron star merger simulations, and extension to smoothed-particle hydrodynamics. Issue 2 (21st May 2021) - Gizzi, D; Lundman, C; O'Connor, E; Rosswog, S; Perego, A
ABSTRACT: We calibrate a neutrino transport approximation, called Advanced Spectral Leakage (ASL), with the purpose of modelling neutrino-driven winds in neutron star mergers. Based on a number of snapshots, we gauge the ASL parameters by comparing against both the two-moment (M1) scheme implemented in the flash code and the Monte Carlo neutrino code sedonu . The ASL scheme contains three parameters, the least robust of which results to be a blocking parameter for electron neutrinos and antineutrinos. The parameter steering the angular distribution of neutrino heating is recalibrated compared to the earlier work. We also present a new, fast and mesh-free algorithm for calculating spectral optical depths, which, when using smoothed-particle hydrodynamics (SPH), makes the neutrino transport completely particle-based. We estimate a speed-up of a factor of ≳100 in the optical depth calculation when comparing to a grid-based approach. In the suggested calibration we recover luminosities and mean energies within 25 per cent . A comparison of the rates of change of internal energy and electron fraction in the neutrino-driven wind suggests comparable accuracies of ASL and M1, but a higher computational efficiency of the ASL scheme. We estimate that the ratio between the CPU hours spent on the ASL neutrino scheme and those spent on the hydrodynamics is ≲0.8 per time-step when considering the SPH code magma2 as source code for the Lagrangian hydrodynamics, to be compared with a factor of 10 from the M1 in flash .